Election and post-election management of the 2021 elections in Uganda. - Makara, Sabiti (Konrad-Adenauer-Stiftung Uganda & South Sudan and The Julius Nyerere Leadership Centre., 2025)
On January 14, 2021, Uganda conducted its fourth multiparty general elections under the National Resistance Movement (NRM) regime, which has governed since 1986. This chapter appraises the performance of the Electoral Commission (EC) and associated institutions in managing these polls, emphasizing key processes such as the electoral roadmap, voter registration and register updates, candidate nominations, freedom to campaign, and results management. It contextualizes the 2021 elections within historical trajectories of electoral administration since independence, including the shift from no-party to multiparty politics in 2005, persistent demands for reforms, and the unprecedented challenges posed by the COVID-19 pandemic. The analysis highlights a persistent trust deficit in the EC stemming from its composition, presidential appointments, and perceived bias toward procedural focus over substantive fairness while questioning whether regular multiparty elections have truly advanced democratic consolidation in Uganda. Drawing on legal frameworks, observer reports, and stakeholder critiques, the chapter underscores how issues like violence, incumbency misuse, and inadequate autonomy undermine electoral integrity, yet notes incremental administrative improvements in areas like voter verification.